KARAKTERISTIK DAN PERHITUNGAN KOEFISIEN SERAPAN (ABSORPTION COEFFICIENT) PROPYLENE GLYCOL SEBAGAI ZAT PENYERAP KELEMBABAN UDARA (DESICCANT) PADA MESIN PENGERING UDARA - Kumara Ari Yuana (Teknoin, 2014)
The objectives of this research are: 1. understanding the characteristics of propylene glycol as desiccant  by manipulating the air volumetric flow rate and propylene glycol volumetric flow rate as desiccant. 2. calculating the optimum operating point of absorption of propylene glycol desiccant at air dryer machine. Theoretically absorption ability of a desiccant  is limited by the ability of the maximum absorbance that  reached when the equilibrium with the surrounding air or saturated conditions is reached. The results indicate that the effect of absorption varies proportionally with volumetric flow rate of desiccant and has a certain optimum point with the volumetric flow rate of air that dried. In this study used two dimensionless scale, i.e. : 1. Coefficient of Absorption (abbreviated AC ).